2015
DOI: 10.5433/1679-0359.2015v36n6sup2p4133
|View full text |Cite
|
Sign up to set email alerts
|

Combining abilities and inbreeding depression in commercial maize hybrids

Abstract: The objective of this study was to evaluate the combining ability and inbreeding depression of commercial maize hybrids for agricultural traits. Twenty-two commercial maize hybrids, 96 F 1 crosses from a partial diallel scheme, 22 S 1 populations and 4 controls were evaluated in a 12x12 simples square lattice experimental setup, totaling 144 treatments, in the municipality of Sabáudia (PR), Brazil, for harvests from 2011/2012 and 2012/2013. Three traits were evaluated: grain yield, plant height and ear height.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Garbuglio et al (2009), studying the genetic variability in these same populations with different sets of S 1 families (and a different number of families), also found results of inbreeding depression below 20% for PH. Similar results were verified by Senhorinho et al (2015) when studying the effects of inbreeding depression in 22 commercial hybrids. In a work with popcorn carried out by Scapim et al (2006), the researchers showed a predominance of additive effect and an inbreeding depression of 10% for plant height and ear height.…”
Section: Resultssupporting
confidence: 70%
“…Garbuglio et al (2009), studying the genetic variability in these same populations with different sets of S 1 families (and a different number of families), also found results of inbreeding depression below 20% for PH. Similar results were verified by Senhorinho et al (2015) when studying the effects of inbreeding depression in 22 commercial hybrids. In a work with popcorn carried out by Scapim et al (2006), the researchers showed a predominance of additive effect and an inbreeding depression of 10% for plant height and ear height.…”
Section: Resultssupporting
confidence: 70%
“…Breeding programs whose objective is to obtain superior hybrids chose to use germplasm with a narrow genetic base for the formation of their base population [Hallauer, Carena and Miranda Filho (2010), Oliboni et al (2013), Souza Neto et al (2015 and Senhorinho et al (2015)]; studies report that commercial single cross hybrids have been used by breeders of outcrossed plants for the formation of segregating populations and is due to the advanced breeding process that these genotypes already utilize. Similarly, this can be an important strategy to generate base populations of autogamous plants such as tomato.…”
Section: Introductionmentioning
confidence: 99%